2018
DOI: 10.7577/seminar.2981
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing future teachers’ competencies for technology integration in education: Turning theory into practice

Abstract: The main aim of this conceptual paper is to provide an overview of effective strategies to support pre-service teachers to adequately integrate ICT in teaching and learning activities. Specifically, the focus is on the strategies included in the SQD (Synthesis of Qualitative Evidence) model: 1) using teacher educators as role models, 2) reflecting on the role of technology in education, 3) learning how to use technology by design, 4) collaboration with peers, 5) scaffolding authentic technology experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…For example, they made several new suggestions regarding collaboration with internal partners, and this may point to the findings by Murtonen and Vilppu (2020) that teachers want collegial support but there may not be enough of it. Tondeur (2018) highlights that integrating technology into teacher design teams can only work if both team and institutional level conditions are observed. This study supports their findings, as it can be concluded that teachers seem to experience organisational, managerial and collegial support important in implementing the ODP education in the whole-of-institution design model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they made several new suggestions regarding collaboration with internal partners, and this may point to the findings by Murtonen and Vilppu (2020) that teachers want collegial support but there may not be enough of it. Tondeur (2018) highlights that integrating technology into teacher design teams can only work if both team and institutional level conditions are observed. This study supports their findings, as it can be concluded that teachers seem to experience organisational, managerial and collegial support important in implementing the ODP education in the whole-of-institution design model.…”
Section: Discussionmentioning
confidence: 99%
“…Also, teachers need support in implementing new approaches and new designs (Chie et al, 2018). Integrating technology into teacher design teams can only work if both team and institutional level conditions are observed (Tondeur, 2018). Teachers must be offered adequate continuing professional development and support (Naidu, 2019) in the pedagogical use of technology for sustained online teaching and development of teachers' agency in digital contexts (Damşa et al, 2021).…”
Section: Previous Researchmentioning
confidence: 99%
“…Worldwide, ICT competencies are considered an essential requirement for teaching and learning in teacher education institutions (Ferrari et al, 2014;Tondeur, 2018;UNESCO, 2017). Teacher educators are expected to demonstrate best practice in the use of ICT in teaching in order to develop teachers who can apply technologies in their teaching at schools.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher educators are expected to demonstrate best practice in the use of ICT in teaching in order to develop teachers who can apply technologies in their teaching at schools. There is consensus across studies that, competencies expected for effective ICT use in teaching and learning form a composite of knowledge domains for subject content, pedagogy and ICTs (Koehler et al, 2013;Tondeur, 2018). However, ICT frameworks adopted different foci to develop these competencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation